Right Temporoparietal Junction Involvement in Autonomic Responses to the Suffering of Others: A Preliminary Transcranial Magnetic Stimulation Study - Miller, Jonas G.; Xia, Guohua; Hastings, Paul D. (Frontiers in Human Neuroscience, 2020)
Functional neuroimaging studies have emphasized distinct networks for social cognition and affective aspects of empathy. However, studies have not considered whether substrates of social cognition, such as the right temporoparietal junction (TPJ), play a role in affective responses to complex empathy-related stimuli. Here, we used repetitive transcranial magnetic stimulation (TMS) to test whether the right TPJ contributes to psychophysiological responding to another person’s emotional suffering. We used a theory of mind functional localizer and image-guided TMS to target the sub-region of the right TPJ implicated in social cognition, and measured autonomic and subjective responses to an empathy induction video. We found evidence that TMS applied at 1 Hz over the right TPJ increased withdrawal of parasympathetic nervous system activity during the empathy induction (n = 32), but did not affect sympathetic nervous system activity (n = 27). Participants who received TMS over the right TPJ also reported feeling more irritation and annoyance, and were less likely to report feeling compassion over and above empathic sadness, than participants who received TMS over the vertex (N = 34). This study provides preliminary evidence for the role of right TPJ functioning in empathy-related psychophysiological and affective responding, potentially blurring the distinction between neural regions specific to social cognition versus affective aspects of empathy.